Pengaruh Tayangan Youtube Podcast Deddy Corbuzier terhadap Kepercayaan Penonton pada Vaksin Covid 19 - Adinda Salsa Bella Chandra Dewi; Indri Rachmawati (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The Covid 19 pandemic occurred in Indonesia, many conspiracy theories have emerged which have been widely discussed by Youtubers in Indonesia. Deddy Corbuzier is now in 3rd position as the richest YouTuber in Indonesia. Deddy Corbuzier often makes video podcasts discussing the Covid 19 conspiracy. One of his videos that is widely discussed is his interview with former Minister of Health, Siti Fadilah. In the video, according to him, the H1N1 virus is a political and economic conspiracy from Bill Gates, who is a global elite and this could have happened in Covid 19. The research entitled